Comparison of Civil Law and Common Law in Australia and Surrounding Countries - Steffany Steffany (Jurnal Daulat Hukum, 2022)
This study aims to determine the legal system can be interpreted in two ways. First, the legal system is defined as a unit of components or elements (sub-systems) as follows: material law-formal law and civil law-public law. Included in this view are those who see the legal system as a unity between various laws and regulations with legal principles. Second, the legal system is defined as a unity of components: legal structure, legal substance, and legal culture. Eric L Richard, an expert in global business law, divides the main legal systems into six legal families: Civil law, Common law, Islamic law, Socialist law, Sub Sahara Africa, and Far east. This research is a qualitative research with a historical juridical approach that describes the legal history of how civil law and common law apply in various countries. By collecting data in the library supported by primary and secondary data according to the chosen topic. In general, based on how law is produced and implemented, there are two legal systems known in the world, namely, civil law and common law. The two legal systems have their own history and differences.